2011
DOI: 10.1007/s11524-011-9599-9
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behavior during Elevated Temperature in Chinese Population

Abstract: The negative impact of extreme temperatures on health is well-established. Individual help-seeking behavior, however, may mitigate the extent of morbidity and mortality during elevated temperatures. This study examines individual help-seeking behavior during periods of elevated temperatures among a Chinese population. Help-seeking patterns and factors that influence behavior will be identified so that vulnerable subgroups may be targeted for health protection during heat crises. A retrospective time-series Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…2.86 days per decade) of heat wave events in 1979-2010, which had accelerated after the 1990s (Luo and Lau 2017). Several studies in Hong Kong observed adverse health effects of heat waves on mortality, hospitalization, and health related help-seeking behavior, which are in line with most studies in other places (Leung et al 2008;Hajat et al 2010;Chan et al 2011a;Chan et al 2011b;Chan et al 2012a;Yi and Chan 2015;Ho et al 2017;Sun et al 2018). For example, Chan et al (2012a) reported that during 1998-2006, a 1°C increase in daily mean temperature above 28.2°C was associated with a 1.8% increase in nonaccidental mortality.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…2.86 days per decade) of heat wave events in 1979-2010, which had accelerated after the 1990s (Luo and Lau 2017). Several studies in Hong Kong observed adverse health effects of heat waves on mortality, hospitalization, and health related help-seeking behavior, which are in line with most studies in other places (Leung et al 2008;Hajat et al 2010;Chan et al 2011a;Chan et al 2011b;Chan et al 2012a;Yi and Chan 2015;Ho et al 2017;Sun et al 2018). For example, Chan et al (2012a) reported that during 1998-2006, a 1°C increase in daily mean temperature above 28.2°C was associated with a 1.8% increase in nonaccidental mortality.…”
Section: Introductionsupporting
confidence: 75%
“…We decided on the two cut-off points due to the following considerations; we found in previous studies that mortality and individual health-seeking behaviors were significantly and positively associated with temperature when values were above 28°C and 31°C respectively. That may roughly reflect the threshold temperatures causing health impacts by hot weather (Chan et al 2011a).…”
Section: Data Collectionmentioning
confidence: 99%
“…A few studies have shown an increase in the number of ambulance emergency call-outs (AECOs) during heat waves in Birmingham, United Kingdom (UK) [ 13 ] and New South Wales [ 14 ]. A high temperature-related ambulance call increase was also observed in Australia [ 15 ] and Hong Kong [ 16 ].…”
Section: Introductionmentioning
confidence: 89%
“…The daily temperature range was calculated as the difference between the maximum and minimum recorded temperatures. Since previous studies suggest the effect of weather on health status tends to be nonlinear [1][2][3][4][5][6], the impact of each of these meteorological variables was modeled as a polynomial function over the respective range of the variable. The degrees of the polynomials were selected using a popular model selection method, the Akaike Information Criterion (AIC) [7].…”
Section: Methodsmentioning
confidence: 99%
“…To this end it is important to study the relation of the service use intensity and the weather conditions (for example, temperature and humidity) based on historical data. A recent work [1] about the association between the frequency of such PE Link calls and meteorological factors found that the effect of temperature on the call frequency was statistically significant and the effect function was roughly U-shaped. When the temperature reached about 30-32°C, the health related PE Link call frequency started to increase.…”
Section: Introductionmentioning
confidence: 99%